Elemental analysis by neutron time-of-flight spectrometry - Strebel, Paul J (Department of Chemistry, 2015)
Among the more common elements for which neutron activation analysis is not sufficiently sensitive, are carbon, nitrogen and oxygen. These elements are so important that they were selected for study in an attempt to extend the advantages of nuclear methods of analysis to their determination. The physical state of a sample submitted to activation analysis frequently determines whether activation analysis is possible or not. Although most solids can readily be submitted to activation analysis, the same does not apply to liquids or gases. In the case of liquids, their radiolytic decomposition may yield gaseous products which could endanger the irradiation facility whilst gases, with few exceptions, present serious technical difficulties for irradiation with reactor neutrons. Clearly the development of a method suitable for the analysis of gases would serve a useful purpose.